2020
DOI: 10.1097/rli.0000000000000689
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of Chest CT in Evaluating the Clinical Severity of COVID-19 Pneumonia: Identifying Critical Cases Based on CT Characteristics

Abstract: This paper can be cited using the date of access and the unique DOI number which can be found in the footnotes. Objectives: To assess the clinical severity of COVID-19 pneumonia using qualitative and/or quantitative chest CT indicators and identify the CT characteristics of critical cases. Materials and Methods: Fifty-one patients with COVID-19 pneumonia including ordinary cases (group A,n=12), severe cases(group B, n=15) and critical cases (group C,n=24) were retrospectively enrolled. The qualitative and quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
140
1
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(161 citation statements)
references
References 33 publications
16
140
1
4
Order By: Relevance
“…The study found that the severe and critical group showed more extensive and severer involvement than those in the moderate group, mainly involving the right lung in the initial CT and the whole lung in the initial and follow-up CT. This nding is similar to previous studies [20,23], which also reported the initial CT score of the whole lung in the severe and critical patients was higher than that in the moderate patients. Furthermore, we found that the patients with severe and critical type progressed rapidly with the greatest severity at the second follow-up CT, and then gradually recovered.…”
Section: Discussionsupporting
confidence: 92%
“…The study found that the severe and critical group showed more extensive and severer involvement than those in the moderate group, mainly involving the right lung in the initial CT and the whole lung in the initial and follow-up CT. This nding is similar to previous studies [20,23], which also reported the initial CT score of the whole lung in the severe and critical patients was higher than that in the moderate patients. Furthermore, we found that the patients with severe and critical type progressed rapidly with the greatest severity at the second follow-up CT, and then gradually recovered.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies [3,4] reported that the degree of consolidation and crazy-paving pattern was highly suggestive for the disease progression/peak, so we used a total sum extent of crazy-paving and consolidation as an indicator for the disease severity. The severity score for the consolidation and crazy-paving was calculated for each lobe using the same criteria (0-4 scores), and the total score for the lungs is the sum of individual lobes (0-20 scores).…”
Section: Qualitative Image Analysismentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19) was firstly diagnosed in Wuhan, China; was announced by the WHO to be caused by a novel coronavirus (SARS-CoV-2); and causes a respiratory disease pandemic [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy, in both studies, CTs had been analyzed manually. Similarly, Lyu et al [7] and Zhang et al [11] showed that the number of lung segments and lobes affected by crazy-paving pattern and consolidation increased with case severity, a fact in line with the increase in LSS and LHOS with increased treatment intensity. The opposite approach was taken by Colombi et al, who quanti ed areas of well-aerated, normal lung to predict adverse outcome in COVID-19 pneumonia [9].…”
Section: Discussionmentioning
confidence: 71%
“…Chest CT is a primary source of early predictive features in COVID-19, because of its high sensitivity for the detection of the disease and the fact that it's a primary modality for imaging of pneumonia [6], There is growing, consistent evidence that CT features are associated with disease severity in COVID-19 based on (semi)manual assessment of pulmonary parameters on chest CT [7][8][9][10][11]. This study builds on these approaches and expands them in three aspects: First, by introducing a fully automated evaluation, which is especially relevant in times of a pandemic spread with heavy workloads on healthcare providers.…”
Section: Introductionmentioning
confidence: 99%